1999
DOI: 10.1111/j.1745-4581.1999.tb00390.x
|View full text |Cite
|
Sign up to set email alerts
|

EFFECTS OF MEMBRANE PROTONOPHORES ON THE ATP CONTENT OF IMMUNOMAGNETIC BEADS CAPTURED ESCHERICHIA COLI O157:H7

Abstract: An approach to rapidly detect the presence of viable Escherichia coli O157:H7 is described. Specific immunomagnetic beads were applied to capture the bacteria in different solutions. The captured bacteria were then lysed by commercially available reagents to release cellular ATP which was detected by firefly luciferin‐luciferase induced chemiluminescence. The bioenergetic status of the bacteria was adjusted by the addition of glucose, a carbon nutrient source, and carbonyl cyanide meta‐chlorophenyl hydrazone (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2001
2001
2006
2006

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…Indeed, the predicted CCCP effects on the cellular ATP level, were verified in our previous studies of E. coli 0157:H7 (Tu et al 1999) and shown to be a measure of cell viability. In the current study, we have expanded the tests on CCCP effects as an indicator of cell viability to those bacteria listed in Table 1.…”
Section: Verification Of Cccp Effectssupporting
confidence: 70%
See 3 more Smart Citations
“…Indeed, the predicted CCCP effects on the cellular ATP level, were verified in our previous studies of E. coli 0157:H7 (Tu et al 1999) and shown to be a measure of cell viability. In the current study, we have expanded the tests on CCCP effects as an indicator of cell viability to those bacteria listed in Table 1.…”
Section: Verification Of Cccp Effectssupporting
confidence: 70%
“…To minimize the potential for outbreaks, the presence of viable pathogens in foods must be rapidly and effectively detected. To this end, we have successfully expanded our previous finding on the influence of CCCP and glucose on the ATP content of E. coli 0157:H7 (Tu et al 1999;Tu et al 2000) to a number of other bacteria. Specifically, the presence of CCCP can decrease the ATP content of viable but not heat-killed cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1 alternative, screening-only tests (Feng 1992;Hartman et al 1992;Fung 1995;Benoit and Donahue 2003). Many rapid methods have been developed for the quick assessment of food samples for the presumptive presence of bacterial pathogens (Gehring et al 1998;Gehring et al 1999;Tu et al 1999;Crawford et al 2000;Tu et al 2002). However, most rapid methods that presumptively detect the presence of pathogenic bacteria in foods do not confirm/identify the presence of targeted bacteria with the exception of some that rely on nucleic acid assays (Deng and Fratamico 1996;Tims and Lim 2003).…”
Section: Introductionmentioning
confidence: 99%